The Role of Bacterial Membrane Vesicles in Human Health and Disease - Villageliu, Daniel N.; Samuelson, Derrick R. (Frontiers in Microbiology, 2022)
Bacterial membrane vesicles (MVs) are nanoparticles derived from the membrane components of bacteria that transport microbial derived substances. MVs are ubiquitous across a variety of terrestrial and marine environments and vary widely in their composition and function. Membrane vesicle functional diversity is staggering: MVs facilitate intercellular communication by delivering quorum signals, genetic information, and small molecules active against a variety of receptors. MVs can deliver destructive virulence factors, alter the composition of the microbiota, take part in the formation of biofilms, assist in the uptake of nutrients, and serve as a chemical waste removal system for bacteria. MVs also facilitate host-microbe interactions including communication. Released in mass, MVs overwhelm the host immune system and injure host tissues; however, there is also evidence that vesicles may take part in processes which promote host health. This review will examine the ascribed functions of MVs within the context of health and disease.